2015
DOI: 10.1007/s00198-015-3319-3
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of personalized supplementation with vitamin D-rich dairy products in the prevention of osteoporotic fractures

Abstract: SummaryTitrated supplementations with vitamin D-fortified yogurt, based on spontaneous calcium and vitamin D intakes, can be cost-effective in postmenopausal women with or without increased risk of osteoporotic fractures.IntroductionThe objective of this study is to assess the cost-effectiveness of the vitamin D-fortified yogurt given to women with and without an increased risk of osteoporotic fracture.MethodsA validated cost-effectiveness microsimulation Markov model of osteoporosis management was used. Three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 43 publications
0
36
0
1
Order By: Relevance
“…Similarly, Ethgen et al also showed that the intake of dairy products is cost-effective in the general population over 70 years in Belgium [31]. Our study is more conservative as we did not incorporate any treatment effect after the year of the intake of fortified dairy products.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, Ethgen et al also showed that the intake of dairy products is cost-effective in the general population over 70 years in Belgium [31]. Our study is more conservative as we did not incorporate any treatment effect after the year of the intake of fortified dairy products.…”
Section: Discussionmentioning
confidence: 97%
“…The fact that at bone level the type 1 collagen matrix is strengthened with the apposition of calcium hydroxyapatite crystals supports the idea that an adequate calcium status is crucial for bone health (13). The dietary calcium intake may be adequate in most individuals, but, there is evidence that in subjects with inadequate calcium and vitamin D intake, the supplementation strategies are useful for preventing osteoporosis related fragility fractures (14,15). Indeed, in the presence of inadequate calcium intake and/or vitamin D production, the latter being fundamental for a proper intestinal calcium absorption, the incipient hypocalcemia leads to a secondary Page 3 of 32 hyperparathyroidism, increased bone turnover, bone loss and increased facture risk (16).…”
Section: Calcium Intakementioning
confidence: 94%
“…Indeed, vitamin D-fortified yogurt given to women with and without an increased risk of osteoporotic fracture is cost-effective in the treatment of osteoporotic fractures in the elderly population 19 . The recommendation to use dairy products as the preferred source of calcium and vitamin D in aging males and females is supported by public health and health economic analyses 20 .…”
Section: Introductionmentioning
confidence: 99%